Positioning of apremilast in treatment of Behçet's disease. Issue 2 (3rd March 2020) - Takeno, Mitsuhiro
Abstract: Behçet's disease is a chronic relapsing inflammatory disorder characterized by oral and genital ulcers, skin lesions, and uveitis. Although the involvement of the gastrointestinal, large vascular, and central nervous systems is less common, it can be fatal at times. To suppress inflammatory exacerbations and recurrences which can cause irreversible organ damage, treatment should be individualized according to the disease phenotype and severity. Apremilast, an oral phosphodiesterase 4 inhibitor, is used to treat psoriasis. The enzyme specific inhibitor increases intracellular cAMP levels, which modulate multiple signaling pathways in both innate and adaptive immunocompetent cells, leading to attenuation of inflammatory responses through the suppression of the functions of various types of immunocompetent cells including Th1 cells, Th17 cells and M1 macrophages. Current evidence shows that apremilast is effective for oral ulcer, the most common symptom of Behçet's disease. An oral ulcer is considered to represent the basic immunopathology of Behçet's disease, because the disease susceptibility genes are shared between Behçet's disease and recurrent aphthous stomatitis. The favorable effects have been documented in other inflammatory diseases with symptoms similar to those of Behçet's disease. The further studies would shed the light on the potential of apremilast for the treatment of Behçet's disease.